2015
DOI: 10.1016/j.rboe.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma (PRP) applied during total knee arthroplasty

Abstract: ObjectiveTo evaluate the efficacy of platelet-rich plasma regarding healing, pain and hemostasis after total knee arthroplasty, by means of a blinded randomized controlled and blinded clinical study.MethodsForty patients who were going to undergo implantation of a total knee prosthesis were selected and randomized. In 20 of these patients, platelet-rich plasma was applied before the joint capsule was closed. The hemoglobin (mg/dL) and hematocrit (%) levels were assayed before the operation and 24 and 48 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…PRP is currently being used to treat acute and chronic tendinopathies in the clinical and surgical settings [7,8]. It also had been certificated by several studies that PRP could improve wound healing in total knee replacements and rotator cuff injuries [9][10][11]. Recently, the clinical injection application of PRP is widespread in various chronic tendinopathies [8,12] which make injectable PRP gel scaffold possible.…”
Section: Introductionmentioning
confidence: 99%
“…PRP is currently being used to treat acute and chronic tendinopathies in the clinical and surgical settings [7,8]. It also had been certificated by several studies that PRP could improve wound healing in total knee replacements and rotator cuff injuries [9][10][11]. Recently, the clinical injection application of PRP is widespread in various chronic tendinopathies [8,12] which make injectable PRP gel scaffold possible.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a less aggressive surgical approach, for example, is now widespread for this purpose but may lead to increased bleeding [ 35 ]. In a previous study, our group showed that the application of platelet-rich plasma in total knee replacement surgery reduced postoperative pain but did not reduce bleeding [ 36 ]. The literature does not show that TXA is effective in controlling pain or movement gain, as our study has shown, in the first 48 hours after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers have found that plateletrich plasma does not reduce blood loss in TKA [69][70][71][72] . In a randomized controlled trial, Morishita et al found that there was no significant difference in blood loss between the platelet-rich plasma group and a control group (826.2 mL vs 830.2 mL; P = 0.96) in TKA 72 .…”
Section: Topical Hemostatic Agentsmentioning
confidence: 92%
“…However, other researchers have found that platelet‐rich plasma does not reduce blood loss in TKA. In a randomized controlled trial, Morishita et al .…”
Section: Intraoperative Strategiesmentioning
confidence: 95%